Optimal pricing policy for ameliorating items considering time- and price sensitive demand. (4th May 2022) - Khedlekar, Uttam Kumar; Singh, Priyanka
ABSTRACT: Amelioration occurs when the utility, value, quality, or quantity of items increases with time. In contrast, deterioration occurs when the quality or quantity of items decreases with time. This study is a purview for both manufacturers and retailers of ameliorating and deteriorating items. In this paper, an integrated inventory model is developed under the influence of amelioration with time and the price varying demand pattern over a fixed time interval. The amelioration is supposed to follow the Weibull distribution, taking into account the infinite time horizon and lack of shortage. Mathematical expressions for the total profit are developed.  The proposed inventory model optimizes the length of time during which there is no demand, the length of time during which the inventory level becomes zero, and it optimizes the initial inventory level to maximize the total profit. We have shown that the profit function is concave with respect to time. Next, we have provided an algorithm to find the optimal solution. Finally, we have delivered numerical examples, conducted sensitivity analysis and provided graphical representations for each case to illustrate the theory of the integrated inventory model for ameliorating items and how the inventory model reacts to changes in parameters.